Situational efficiency parameters of succesful and unsuccessful top male basketball teams in the Olympic tournament games in London 2012 - Milanovic, D.; Stefan, L.; Skegro, D. (Baltic Journal of Sport and Health Sciences, 2016)
Background. The purpose of this study was to determine differences in situational efficiency parameters that differentiate male basketball teams according to outcome. Sample of entities consisted of 38 games played in the Olympic Games in London 2012. Methods. Situational efficiency variables that affected the final outcome were comprised of 13 parameters. Differences between successful and unsuccessful teams were obtained using Student t-test. Also, overall differences between teams were analysed applying multivariate analysis of variance (MANOVA) and discriminant analysis with standardized canonical coefficients (SCC). Significant value was set up at p . .05. Results. Results showed overall statistical differences in situational parameters between teams (p < .001). Also, discriminant function showed that situation parameters 2 pts-fail (F-value -14.82, SCC = .0.967, p < .001), 3 pts-fail (F-value = 5.57, SCC = .0.403; p < .05), offensive rebounds (F-value . 16.38, SCC = 0.943, p < .001), defensive rebounds (F-value = 6.66, SCC = 0.822, p < .05), turnovers (F-value = 14.03, SCC = .0.608, p < .001) and steals (F-value = 4.78, SCC = 0.425, p < .05) differentiated most of the teams according to outcome. Conclusion. On the basis of the obtained results we suggest that winning teams had technical-tactical parameters on higher level due to better timing of sports fitness with adequate resting periods and type of training process.